2023
DOI: 10.1101/2023.02.06.527192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overcoming clinical resistance to EZH2 inhibition using rational epigenetic combination therapy

Abstract: Essential epigenetic dependencies have become evident in many cancers. Based on functional antagonism between BAF/SWI/SNF and PRC2 in SMARCB1-deficient sarcomas, we and colleagues recently completed the clinical trial of the EZH2 inhibitor tazemetostat, leading to its FDA approval. However, the principles of tumor response to epigenetic therapy in general, and tazemetostat in particular, remain unknown. Using functional genomics of patient tumors and diverse experimental models, we define molecular mechanisms … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 108 publications
(182 reference statements)
1
17
0
Order By: Relevance
“…). Using CRISPR gene editing, we generated isogenic RB1 wild-type and RB1 del mutant G401 cells and confirmed correct biallelic RB1 inactivating mutations and consequent loss of RB1 protein expression, using the AAVS1 safe harbor as a negative control (8). In prior work, we found that defects in the RB1/E2F axis, including mutations of RB1, cause TAZ resistance (8).…”
Section: Figure 1dmentioning
confidence: 76%
See 4 more Smart Citations
“…). Using CRISPR gene editing, we generated isogenic RB1 wild-type and RB1 del mutant G401 cells and confirmed correct biallelic RB1 inactivating mutations and consequent loss of RB1 protein expression, using the AAVS1 safe harbor as a negative control (8). In prior work, we found that defects in the RB1/E2F axis, including mutations of RB1, cause TAZ resistance (8).…”
Section: Figure 1dmentioning
confidence: 76%
“…We found that in addition to the expected upregulation of Polycomb gene sets, EZH2 inhibition in G401 rhabdoid tumor cells with TAZ for 11 days also caused a significant increase in the expression of PGBD5 (mean fold-increase of 6.6 and Student’s t-test p = 1.2E-7; Figure 1D ). Using CRISPR gene editing, we generated isogenic RB1 wild-type and RB1 del mutant G401 cells and confirmed correct biallelic RB1 inactivating mutations and consequent loss of RB1 protein expression, using the AAVS1 safe harbor as a negative control (8). In prior work, we found that defects in the RB1/E2F axis, including mutations of RB1 , cause TAZ resistance (8).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations